Education for Sustainable Development Goals (ESDG): What Is Wrong with ESDGs, and What Can We Do Better? - Helen Kopnina (MDPI AG, 2020)
This article will discuss social, environmental, and ecological justice in education for sustainable development (ESD) and Education for Sustainable Development Goals (ESDG). The concept of sustainable development and, by extension, the ESD, places heavy emphasis on the economic and social aspects of sustainability. However, the ESD falls short of recognizing ecological justice, or recognition that nonhumans also have a right to exist and flourish. An intervention in the form of an undergraduate course titled Politics, Business, and Environment (PBE) will be discussed. As part of this course, students were asked to reflect on the three pillars of sustainable development: society, economy, and environment, linking these to the fourth concept, ecological justice or biospheric egalitarianism. Biospheric egalitarianism is characterized by the recognition of intrinsic value in the environment and is defined as concern about justice for the environment. Some of the resulting exam answers are analyzed, demonstrating students' ability to recognize the moral and pragmatic limitations of the anthropocentric approach to justice. This analysis presents ways forward in thinking about the role of "ecological justice" as the ultimate bottom line upon which both society and economy are based.